Implementation of Community Based Curriculum Development - Ima Muslimatul Amanah; Andi Sukandi; Cecep Hilman (P3M IAI Nusantara Batang Hari, 2023)
Society is always changing and will continue to change from time to time. Society in the modernization era is very much different from society before this, and will be different from society in our future generations. There are also more and more demands from society in order to balance the current pattern and lifestyle. The change will obviously affect our way of life and way of thinking. This vast world is no longer an obstacle to human communication. Everything that is considered important by humans, will be published on social media. Advances in science and technology can spoil humans. As we all know, that the characteristic of society is dynamic. The community has a very large role and responsibility in the curriculum development process in educational units considering that schools are miniatures of society which will become the next generation in preserving cultural heritage. Community involvement in the curriculum development process includes the formulation of community-based curriculum design, planning, implementation and evaluation. Thus, the curriculum must be elastic and flexible as well as dynamic following the flow of developments that humans continue to strive for. A dynamic curriculum is important for maintaining human survival, because it is functional and prepares children to face problems in the society where they live. The focus in this paper is laying out patterns, concepts, characteristics and stages in the development of a community-based curriculum